Mechanical simulation analysis of lightweight blades using glass fiber phenolic resin composites. Issue 3 (May 2021) - Zhu, Lingfeng; Xu, Jingfeng; Zhang, Wenze
Abstract: This paper uses simulation methods to verify the reliability of applying glass ferroaluminium alloy laminates to subway fan blades. Through the force analysis of its blades, it is found that the material has a wider application prospect in subway fan blades, and it can achieve better energy-saving effects than the existing aluminium alloy blades.